Investigation of Coronavirus Disease 2019 (COVID-19) Outbreak in Waeng District, Narathiwat Province - Sakdirath, ์Nattanai; Siriphraiwan, Sitthiporn (Princess of Naradhiwas University Journal, 2021)
The objective of descriptive epidemiological study by reviewing was 1) to find the source of the disease and the people which exposed to the corona virus 2019, 2) to describe the nature of the disease distribution by person, time and place, 3) to confirm the diagnosis and the outbreak of corona virus 2019, and 4) to determine appropriate measures in disease prevention and control planning. The percentage statistics retrospective disease situation before 14 March 2020 was recorded. Collecting data of the patient was recorded by confirming data from medical, investigating reports, and searching for additional patients in all index exposure patients. The performing active finding was done in seven groups of population. Respiratory samples were collected for RT-PCR testing and in case of negative contact in the family of RT-PCR, blood samples were collected at the fingertips for SARS CoV-2, IgM or IgG antibody by Rapid testing. The results found that 14 cases were confirmed with RT-PCR and 9 categorized as a positive result with SARS-CoV-2 IgG. Five cases were categorized as positive SARS-CoV-2 IgG. Four cases were in the reporting system. Among the 10 Index cases exposed, the infection rate was 5.95%. The highest infection rate was 85.71%, 1 case RT-PCR positive and 5 cases Ab IgG positive. The infection rate was 4.00% of hospital exposure and 1.16% of community contact. Three reported system patients were returning from abroad in 14 days prior to illness (75%). Index cases had a history of returning from abroad 51 days before the illness. The source of disease of the Index case patients did not find a clear source of disease. Local transmission of disease through close, unprotected family contact was an important factor. Effective disease transmission control measures require adequate state quarantine facilities. People in the area cooperate to strictly adhere to social distancing measures, and hospitals must have internal control measures to prevent the spread of infection by both service providers and service recipients.